Necessity for lifelong follow‐up of patients with familial paraganglioma syndrome: A case report. Issue 12 (6th July 2015) - Persky, Michael J.; Adelman, Mark; Zias, Elias; Myssiorek, David
Abstract: Background: Patients with established familial paraganglioma (PGL) syndrome may have multiple metachronous lesions. This article illustrates, via imaging and findings, the need for lifetime follow‐up of patients with familial PGL syndromes. Methods: Patients' medical charts and radiological images were reviewed in a retrospective analysis. Results: Over the course of 18 years, this patient developed 2 simultaneous carotid PGLs, a cardiac PGL, and a biochemically active interaortocaval PGL. Conclusion: PGLs do not necessarily occur simultaneously in patients with familial PGL syndrome. Lifelong observation is needed to detect these lesions before they become large and symptomatic. Lack of biochemical activity is not a predictor of future lesions being inactive. Cardiac PGLs are rare and require resection. © 2015 Wiley Periodicals, Inc. Head Neck 37: E174–E178, 2015